The influence of flap design on patients' experiencing pain, swelling, and trismus after mandibular third molar surgery: a scoping systematic review - Gennaro DE MARCO; Alessandro LANZA; Corina M. CRISTACHE; Estefani B. CAPCHA; Karen I. ESPINOZA; Rosario RULLO; Rolando VERNAL; Emilio A. CAFFERATA; Fabrizio DI FRANCESCO (University of São Paulo, 2021)
Abstract Third molar removal surgery usually comes accompanied by postoperative discomfort, which could be influenced by the surgical approach chosen. This scoping systematic review aimed at compiling the available evidence focused on the influence of flap design, including envelope flap (EF), triangular flap (TF), and modified triangular flap (MTF), on postoperative pain, swelling, and trismus, as primary outcome measures, and any result mentioning healing promotion or delay, as secondary outcome measure, after mandibular third molar extraction surgery. An electronic search, complemented by a manual search, of articles published from 1999 to 2020 was conducted in the Medline (PubMed), EMBASE and Web of Science databases including human randomized controlled trials, prospective, and retrospective studies with at least 15 patients. The risk of bias of the included studies was assessed either with the Cochrane's Risk of Bias tool or with the Newcastle-Ottawa scale. Every step of the review was performed independently and in duplicate. The initial electronic search recovered 2102 articles. After applying the inclusion criteria, 12 articles were included. For patient's perceived postoperative pain, TF and MTF frequently reported better results than EF. For swelling, the literature is divided, despite a trend favoring EF. For trismus, data showed that its occurrence is mostly associated with the duration of the surgery rather than with the chosen flap. For healing, the limited data is inconclusive. Finally, randomized studies showed a high risk of bias, whereas nonrandomized studies were mostly of good quality and low risk of bias. Although there was no clear consensus regarding the influence of different flap designs for third mandibular molar extraction on postoperative clinical morbidities; the surgeon's experience, estimated surgical difficulty, molar position and orientation, and surg ery duration should be considered when choosing among the different flap designs.